Technology Entrepreneurship (ENT600) IvVLuggage / Fazira Sahira Supardi … [et al.] - Supardi, Fazira Sahira; Abu Hassan, Haslinda; A. Karim, Noor Madina; Md Zainal Abidin, Nur Camellia Emily Shazleen; Mohd Kamal, Nur Farzana (2016)
The product to be developed is IvVluggage that features vacuum bag with piston, digital selfweight, GPS with LugLoc.app application and 360-degree wheel. These features are developed to overcome the common problems such as inefficient space used or hard to fit in lot of clothes, extra charges fee due to overweight and hard to identify luggage in crowds.